AUDIT KOMUNIKASI TERHADAP SOSIALISASI PROGRAM KONSERVASI TANAH DAN AIR BERKELANJUTAN DI KABUPATEN TEMANGGUNG - Setyawati, Indra; Lestari, Puji; Sosiawan, Edwi Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Temanggung Regency, as an upstream area, has critical land, so the Regional Government has launched a Sustainable Soil and Water Conservation Program. The purpose of the audit communication for this socialization program is to diagnose the challenges and barriers that occur in the socialization process of a sustainable soil and water conservation program in Temanggung Regency and provide recommendations for future socialization. This research employs a concurrent embedded mixed methods design, with qualitative methodology as the primary method and quantitative methodology as the secondary method, in a proportion of 80% qualitative and 20% quantitative. Based on the results of the diagnosis, it is known that there is interference, which is a factor inhibiting the success of the socialization carried out in each observation unit. Several recommendations were made based on the audit that had been carried out. Namely, communicators must improve interpersonal communication abilities/skills and implement interactive communication to create more effective two-way communication. The context of the socialization implementation is carried out at the right time to support the effectiveness of the message's performance. Messages are packaged in clear, straightforward, intact, and simple language but must be supplemented with content according to program implementation instructions. The frequency needs to be increased, and a unique account for the conservation program is created. Written and bureaucratic communication must be maintained, but the effectiveness of the communication network needs to be increased through WhatsApp groups and other media. It is necessary to evaluate community feedback.